12 - Appendix III: ECOWAS Six-Month Peace Plan for Sierra Leone, 23 October 1997-22 April 1998 (Schedule of Implementation) - Journal System (Africa Development, 1997)
Appendix III: ECOWAS Six-Month Peace Plan for Sierra Leone, 23 October 1997-22 April 1998 (Schedule of Implementation)